Secure Web Application for Clinic - Nurshahira Binti Othman; Amna Binti Saad (Journal of Computing Technologies and Creative Content, 2023)
In the era of globalization, technological advancements influence how people live their lives. For example, the online scheduling is an amazing technology add-on for outpatients looking for convenience during their treatment phase. However, the web application must be patched with security to develop a secure system. Rapid Application Development Model (RAD) is the methodology in this project since it is a prototype. This research presents a study of Secure Web Application for Clinic which is a web-based application system developed for allowing the outpatient to make an online booking appointment using the system, and the admin can add a session for the doctor or add a new doctor to the clinic. In addition, the doctor can be remotely updated on the latest session or appointments that have been made. Furthermore, this research paper will study the web’s security implementation, which is OWASP’s Top 10 2021 guideline for developing a secure web application and protecting the patient’s sensitive data, such as their password for authentication, by using a cryptography method, MD5. Finally, this research paper tests the security as it results that the OWASP guideline is significant for assuring the system’s reliability and may be implemented as an example by other web developers, particularly when developing web applications for the healthcare industry.